2010
DOI: 10.1103/physreva.81.013833
|View full text |Cite
|
Sign up to set email alerts
|

Coherent-population-trapping resonances with linearly polarized light for all-optical miniature atomic clocks

Abstract: We present a joint theoretical and experimental characterization of the coherent population trapping (CPT) resonance excited on the D 1 line of 87 Rb atoms by bichromatic linearly polarized laser light. We observe high-contrast transmission resonances (up to ≈25%), which makes this excitation scheme promising for miniature all-optical atomic clock applications. We also demonstrate cancellation of the first-order light shift by proper choice of the frequencies and relative intensities of the two laser-field com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 25 publications
0
69
1
2
Order By: Relevance
“…The light shift of the dark resonance can be qualitatively explained from the coupling to the non-resonant excited state hyperfine sublevel (which in our case is F e = 2). In the lin lin configuration the light shift can be positive or negative depending on the electromagnetic field spectral distribution and on the one-photon optical detuning [41]. We have measured a negative light shift mainly due to the transitions |F g = 2,m F = ±1 → |F e = 2,m F = 0 .…”
Section: Light Shift Of the Dark Resonancementioning
confidence: 75%
“…The light shift of the dark resonance can be qualitatively explained from the coupling to the non-resonant excited state hyperfine sublevel (which in our case is F e = 2). In the lin lin configuration the light shift can be positive or negative depending on the electromagnetic field spectral distribution and on the one-photon optical detuning [41]. We have measured a negative light shift mainly due to the transitions |F g = 2,m F = ±1 → |F e = 2,m F = 0 .…”
Section: Light Shift Of the Dark Resonancementioning
confidence: 75%
“…The detection of high contrast resonances with optimized CPT interaction schemes is known to be improved with high operating laser intensities [3,5,8]. Nevertheless, in continuous regime, high intensities broaden the CPT resonance line, limiting the clock short-term frequency stability and increasing the light shift.…”
Section: Introductionmentioning
confidence: 99%
“…Yudin et al [19] showed that a recently studied lin||lin configuration is a promising candidate for EIT atomic clock applications [20][21][22][23]. The amplitude of the magnetoinsensitive EIT resonance is sensitive to the magnetic field direction and has a universal maximum when the laser polarization vector, E, is orthogonal to the plane formed by the magnetic field vector, B, and laser wave vector, k. Thus, measureing the resonance amplitude while rotating the laser polarization should provide information about magnetic field direction.…”
mentioning
confidence: 99%
“…4(b)]. The resonance asymmetry can be reduced by optimizing the laser detuning [22] and by operating at higher magnetic fields.…”
mentioning
confidence: 99%
See 1 more Smart Citation